2007
DOI: 10.1123/jsep.29.2.225
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behavior: Predicting Physical Activity in Mexican American Children

Abstract: Theoretically grounded research on the determinants of Mexican American children’s physical activity and related psychosocial variables is scarce. Thus, the purpose of our investigation was to evaluate the ability of the theory of planned behavior (TPB) to predict Mexican American children’s self-reported moderate-to-vigorous physical activity (MVPA). Children (N = 475, ages 9-12) completed questionnaires assessing the TPB constructs and MVPA. Multiple regression analyses provided moderate support for the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
4
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 43 publications
12
59
4
14
Order By: Relevance
“…Although some studies have reported the significant role of perceived behavioral control in shaping healthy behaviors (19,20), our findings revealed no significant changes in the score of this construct after the study intervention (P = 0.05). It is noteworthy to mention that there are many real or perceived financial, psychological, environmental, and normative barriers to preventive behaviors.…”
Section: Discussioncontrasting
confidence: 45%
“…Although some studies have reported the significant role of perceived behavioral control in shaping healthy behaviors (19,20), our findings revealed no significant changes in the score of this construct after the study intervention (P = 0.05). It is noteworthy to mention that there are many real or perceived financial, psychological, environmental, and normative barriers to preventive behaviors.…”
Section: Discussioncontrasting
confidence: 45%
“…Students' answers for strenuous, moderate, and mild exercise were then multiplied by 9, 5, and 3 METs, respectively (Godin & Shephard, 1985). The GLTEQ has been successfully employed with similar aged minority children in previous research (Biddle & Goudas, 1996;Hausenblas et al, 2002;Martin et al, 2007Martin et al, , 2005Martin et al, , 2008Sallis, Buono, Roby, Micale, & Nelson, 1993) and has been validated with children using objective measures of PA (Jacobs, Ainsworth, Hartman, & Leon, 1993).…”
Section: Physical Activity Variablementioning
confidence: 99%
“…All questions were developmentally appropriate and have been used with similarly aged children before (e.g., Duncan, Duncan, & Strycker, 2005;Martin et al, 2005Martin et al, , 2007Martin et al, , 2008.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These determinants include attitudes/beliefs (an individual's perception toward a behavior), perceived norms (including social pressures within a culture or family), and perceived behavioral control (self-efficacy or an individual's belief about the ease or difficulty of performing a behavior). The PCBT has been used to predict behaviors such as weight loss, physical activity and self-efficacy for healthy eating in Mexican-American populations [39][40][41][42].…”
Section: Methodsmentioning
confidence: 99%